The Differences of Color Adjectives in Modern Chinese and its Cause - Asavaratana, Warisa (Journal of Sinology (วารสารจีนวิทยา), 2014)
Color adjectives (CA) are normally used to describe the colors of objects. But while taking a look at lexical level and syntactic level, we found that each of them has many differences. The purpose of this research is to find the differences of twelve monosyllabic adjectives of colors, in terms of syntactic, focusing on their abilities to reduplicate, their syntactic functions (SF) before and after reduplicating. The result shows that these twelve color adjectives have the different syntactic functions. These differences can initially be explained by adopting cognitive linguistics theory, which are the prominence of focal color and the prototype category theory.